The Leadership and the institutional excellence at the Saudi Arabia's Universities in the light of the vision 2030: An applied study on the academicians - et. al., Yousef A. Baker El-Ebiary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to identify the demographic variables that are effective in leading the academic staff in general and to identify the most important obstacles that may prevent the empowerment of academics in various sectors in terms of leading projects in an academic way. Descriptive analyzes are used to find the level of academic leadership. We do not find statistically significant differences in academic leadership in Vision 2030 due to demographic variables such as gender, age, degree, place of residence, nature of work and experience. It was found that the most effective obstacle to academic empowerment in Saudi Arabia is the weakness of some equipment and capabilities that may provide the academic segment in some universities. The study recommends continuing to support decision-makers in state institutions in general and educational institutions in particular to empower academics in the academic aspects and activate the media role in continuing awareness of the importance of leading academics in the practical side and expanding the provision of vocational training